2014
DOI: 10.15282/ijame.9.2014.2.0124
|View full text |Cite
|
Sign up to set email alerts
|

Four-Sided Lid-Driven Cavity Flow using Time Splitting Method of Adams-Bashforth Scheme

Abstract: In this paper, a second order Adams-Bashforth method is proposed to simulate foursided square lid-driven cavity flow. The convective term and diffusive term in Navier-Stokes equations are solved using a finite central difference scheme and the unsteady term is solved using the Adams-Bashforth method. All of the flow is simulated at below critical Reynolds numbers in a square cavity with an isothermal condition and the same speed for all walls. In this study, the flow structure for a four-sided lid-driven cavit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…We have compared the locations of vortices which occur in the vicinity of four walls in Table 2. It is found that our results and those of [9,10], are in good agreement.…”
Section: Code Validationsupporting
confidence: 85%
See 2 more Smart Citations
“…We have compared the locations of vortices which occur in the vicinity of four walls in Table 2. It is found that our results and those of [9,10], are in good agreement.…”
Section: Code Validationsupporting
confidence: 85%
“…11 and 12). Also, to determine the accuracy of our present numerical scheme, we have studied the four-sided, lid-driven square cavity problem investigated by Perumal and Dass [9], and Azwadi et al [10]. We have compared the locations of vortices which occur in the vicinity of four walls in Table 2.…”
Section: Code Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…The geometric simplicity of the problem makes it ideal for numerical discretization and computations, while the discontinuous mathematical boundary condition for the velocity leads to singular properties close to the corners of the moving lid at the two neighboring stationary walls. Azwadi et al (2014) studied the cavity flow for four-sided square lid-driven cavity flow by using a second-order Adams-Bashforth method. They simulated the flow at below critical Reynolds numbers in a square cavity with an isothermal condition and the same speed for all walls.…”
Section: Introductionmentioning
confidence: 99%
“…They have obtained the numerical solutions for the flow variables as well as local and average Nusselt numbers (to analyze the heat transfer inside the cavity) using the QUICK scheme of finite volume methods. Azwadi et al [3] have used the Adams-Bashforth method to investigate the fluid flow inside a four-sided lid-driven square cavity, at below the critical Reynolds numbers (Re ≤ 127) . Bagai et al [4] have examined the problem of heat and mass transfer of a 2-D unsteady incompressible fluid flow in a four-sided lid-driven square cavity with the help of stream functionvorticity formulation and ADI method.…”
Section: Introductionmentioning
confidence: 99%